Genetic parameters, genetic trends, and principal component analysis for productive and reproductive traits of Guzera beef cattle - Tramonte, Nicole Colucci [UNESP]; Grupioni, Natalia Vinhal [UNESP]; Stafuzza, Nedenia Bonvino [UNESP]; Freire Guidolin, Diego Gomes; Savegnago, Rodrigo Pelicioni [UNESP]; Framartino Bezerra, Luiz Antonio; Lobo, Raysildo Barbosa; Munari, Danisio Prado [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2019)
The objectives of this study were to estimate genetic parameters and genetic trends and perform principal component analysis for the following traits: body weight adjusted at 210 days of age (W210), one year (W365), and yearling or 450 days of age (W450); weight gain from birth to weaning or 210 days of age (WGBW), from weaning to 365 days of age (WGW365), and from one year to yearling (WGY); and scrotal circumference adjusted at 365 (SC365) and 450 (SC450) days of age of Guzera beef cattle. Variance components were estimated under a two-trait animal model using the restricted maximum likelihood method. The fixed effects included in the model were birth season, contemporary group, and covariable age of dam at calving as linear and quadratic effects. Heritability estimates ranged from 0.10 (WGY) to 0.41 (W450 and SC450). The studied traits could be used as selection criteria because of their sufficient additive genetic variability to respond to the selection process. However, lower selection efficiency is expected for WGBW and WGY. Genetic trends studied were significant for all traits, except WGY. The W365 and W450 traits belonged to the Genetic Merit Total index and responded to selection with favorable genetic gain per year. The traits that were not included in the selection index showed favorable positive genetic correlations attributed to the indirect selection processes. The principal component analysis identified two groups of traits. The first group related to body weight and weight gain and the second related to the scrotal circumference, indicating that selection could be applied to one group of traits within each observed group. The genetic gains were attributed in the same direction for the other traits belonging to the groups. Thus, we recommend selecting animals for W365 based on first group, and SC365 based on second.
Keywords: animal breeding; Bos taurus indicus; genetic correlation; heritability